Magnetic Alignment for Plasmonic Control of Gold Nanorods Coated with Iron Oxide Nanoparticles - Rizvi, Mehedi H.; Wang, Ruosong; Schubert, Jonas; Crumpler, William D.; Rossner, Christian; Oldenburg, Amy L.; Fery, Andreas; Tracy, Joseph B. (Advanced Materials, 2022)
Plasmonic nanoparticles that can be manipulated with magnetic fields are of interest for advanced optical applications, diagnostics, imaging, and therapy. Alignment of gold nanorods yields strong polarization-dependent extinction, and use of magnetic fields is appealing because they act through space and can be quickly switched. In this work, cationic polyethyleneimine-functionalized superparamagnetic Fe3O4 nanoparticles (NPs) are deposited on the surface of anionic gold nanorods coated with bovine serum albumin. The magnetic gold nanorods (MagGNRs) obtained through mixing maintain the distinct optical properties of plasmonic gold nanorods that are minimally perturbed by the magnetic overcoating. Magnetic alignment of the MagGNRs arising from magnetic dipolar interactions on the anisotropic gold nanorod core is comprehensively characterized, including structural characterization and enhancement (suppression) of the longitudinal surface plasmon resonance and suppression (enhancement) of the transverse surface plasmon resonance for light polarized parallel (orthogonal) to the magnetic field. The MagGNRs can also be driven in rotating magnetic fields to rotate at frequencies of at least 17 Hz. For suitably large gold nanorods (148 nm long) and Fe3O4 NPs (13.4 nm diameter), significant alignment is possible even in modest (<500 Oe) magnetic fields. An analytical model provides a unified understanding of the magnetic alignment of MagGNRs.
CRIS-Team Scopus Importer:2023-03-20
Keywords: dipolar interactions; gold nanorods; iron oxide; magneto-optical effect; surface plasmon resonance